Association between food consumption and the Quality of Diet Index Adapted for pregnant women - Ana Raquel Ernesto Manuel Gotine; Mariana De Santis Filgueiras; Sarah Aparecida Vieira Ribeiro; Raquel Maria Amaral Araújo; Patrícia Feliciano Pereira (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to investigate the association between the Índice de Qualidade da Dieta Adaptado para Gestantes (IQDAG) (Quality of Diet Index Adapted for Pregnant Women) with food consumption, lifestyle and health information. Methods: cross-sectional study with 110 pregnant women assisted at a public health service. Sociodemographic, nutritional and health data were collected from medical records. Food consumption was investigated through the usual intake, for a nutritional analysis, DietPro® program version 6.1 was used. Quality ofdiet was assessed using the IQDAG. Multinomial logistic regression was used to investigate an association between food consumption and IQDAG. Results: the average total score of the IQDAG was 61.3 (±26.1), this is the best quality of the diet. After adjusting for age, schooling and physical activity, the highest consumption of vitamin A (OR=1.04; CI95% = 1.02-1.07) and B2 (OR=2.63; CI95% = 1.19-5.70) was associated with a greater chance of having a better quality of diet (3rdtertile of the IQDAG). Conclusions: pregnant women with better quality of diet had higher intakes of vitamins A and B2. However, other population-based studies are suggested to more broadly in verify its association with food consumption and its ability to identify adherence to nutritional recommendations.